The first comprehensive safety study of Magnéli phase titanium suboxides reveals no acute environmental hazard. Issue 4 (28th February 2019) - Jemec Kokalj, Anita; Novak, Sara; Talaber, Iva; Kononenko, Veno; Bizjak Mali, Lilijana; Vodovnik, Maša; Žegura, Bojana; Eleršek, Tina; Kalčikova, Gabriela; Žgajnar Gotvajn, Andreja; Kralj, Slavko; Makovec, Darko; et al.
Abstract : This study provides the first evidence that the tested Magnéli TiO x are not acutely hazardous. Abstract : Magnéli phase titanium suboxides (Magnéli TiO x ) are novel conductive materials with great industrial potential. This is the first comprehensive investigation to provide an extensive dataset for hazard characterisation of Magnéli TiO x using six standardised test organisms and two human cell lines. Three Magnéli TiO x particles and three anatase crystalline phase TiO2 nanomaterials with different primary powder sizes, but similar hydrodynamic diameters in biological media, were investigated. All Magnéli TiO x and TiO2 nanomaterials induced negligible biological responses in Tetrahymena thermophila, Lemna minor, Artemia franciscana and Danio rerio . Adverse effects were found only at 100 mg L −1 where approximately 50% endpoint inhibition was recorded in the cases of Daphnia magna exposed to two Magnéli TiO x, Pseudokirchneriella subcapitata exposed to all three Magnéli TiO x and HepG2 cells exposed to one type of Magnéli TiO x . This study provides the first evidence that the tested Magnéli TiO x are not acutely hazardous according to existing EU classification for conventional chemicals.